2022
DOI: 10.3389/fimmu.2022.862415
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interleukin-17A in the Pathomechanisms of Periodontitis and Related Systemic Chronic Inflammatory Diseases

Abstract: Periodontitis is a chronic inflammatory and destructive disease caused by periodontal microbial infection and mediated by host immune response. As the main cause of loosening and loss of teeth in adults, it is considered to be one of the most common and serious oral diseases in the world. The co-existence of periodontitis and systemic chronic inflammatory diseases such as rheumatoid arthritis, psoriasis, inflammatory bowel disease, diabetes and so on is very common. It has been found that interleukin-17A (IL-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 148 publications
1
12
0
Order By: Relevance
“…Our results indicate that higher levels of IL-17 are inversely related to periodontitis risk. The present study, along with previous research, 30,31 implies that IL-17 plays a protective role in initial periodontal disease development. Studies in individuals with defects in the IL-17/Th17 pathway have shown that IL-17 is vital to counter Candida albicans infections 9 and IL-17R mediates host defense against Porphyromonas gingivalis-induced bone loss.…”
Section: Discussionsupporting
confidence: 85%
“…Our results indicate that higher levels of IL-17 are inversely related to periodontitis risk. The present study, along with previous research, 30,31 implies that IL-17 plays a protective role in initial periodontal disease development. Studies in individuals with defects in the IL-17/Th17 pathway have shown that IL-17 is vital to counter Candida albicans infections 9 and IL-17R mediates host defense against Porphyromonas gingivalis-induced bone loss.…”
Section: Discussionsupporting
confidence: 85%
“…Th17 mainly secrete IL-17 and IL-22 and intervenes in developing chronic immune-mediated inflammatory diseases, including RA (Feng et al, 2022). IL-17A is a potent inducer of matrix metalloproteinases, recruits neutrophils to the joint, and stimulates osteoclastogenesis resulting in cartilage and bone destruction (Amdekar et al, 2013;Pineda et al, 2014;Lee et al, 2015;du Teil Espina et al, 2019;Huang et al, 2019;Marazzato et al, 2022).…”
Section: Gut Microbiota Can Modulate the Th17/treg Balancementioning
confidence: 99%
“…1 Severe periodontitis can eventually lead to loosening and loss of teeth, which seriously affects people's quality of life. 2 Elimination of pathogens and re-establishment of normal oral flora have been the focus of periodontitis treatment. 3 The primary standard treatment methods for periodontitis are scaling and subgingival scraping to thoroughly remove plaque and calculus from the gums and control the inflammation of the gums.…”
Section: Introductionmentioning
confidence: 99%
“…Periodontitis is a chronic progressive inflammatory disorder featured by gingival inflammation and alveolar bone resorption, initiated by plaque biofilm, and promoted by various environmental and genetic factors 1 . Severe periodontitis can eventually lead to loosening and loss of teeth, which seriously affects people's quality of life 2 . Elimination of pathogens and re‐establishment of normal oral flora have been the focus of periodontitis treatment 3 .…”
Section: Introductionmentioning
confidence: 99%